Ultrasound‐Assisted Extraction (UAE) for the Utilization of Deep‐Water Pink Shrimp (Parapenaeus longirostris) Processing Waste: Comprehensive Characterization of Carotenoid Astaxanthin Rich Extract - Çiğdem Dikel; Yasemen Yanar (Veterinary Medicine and Science)
ABSTRACT In this study, astaxanthin extract was obtained from deep‐water pink shrimp (Parapenaeus longirostris) shell wastes by ultrasound‐assisted extraction method using six different organic solvents, characterized and compared with commercial astaxanthin standard. Astaxanthin extractions were performed under different time conditions (2 and 4 h) using selected apolar/polar solvents (petroleum ether, hexane, isopropanol, ethanol, methanol, acetone). All extracts were quantitatively tested by high‐performance liquid chromatography. The results show that solvents with higher polarity are more suitable for astaxanthin extraction, and the effect of time on extraction yield varies with the type of solvent. The highest astaxanthin concentration was obtained after 2 h of extraction using methanol (310 ±2.00 µg/g) and the lowest value after 4 h of extraction using petroleum ether (104 ± 30.00 µg/g) (p < 0.05).The UV–Vis spectra of astaxanthin extract showed maximum absorbance in the visible region in the range of 480–520 nm, which is the characteristic absorbance of astaxanthin. Fourier transform infrared spectrometry (FTIR) spectrometry was used to confirm the fingerprint region of astaxanthin extract with C = O stretching vibration, methyl group (aliphatic) (–CH), ketone group (–C = O) (6‐membered ring), alkenes (C–C, C = C) and C–CH3 stretching bonds. In the Raman spectrum, all characteristic values reflect the molecular vibrations of the conjugated polyene chain and its bonded groups, providing a distinct spectral fingerprint for the astaxanthin extract.